A Patient with an Ileocecal MiNEN and a Synchronous Squamous Non-Small-Cell Lung Cancer: Case Report and Review of the Literature - Santiago Teran; Maria Camara Jurado; Juan Antonio Nuñez Sobrino (Case Reports in Oncological Medicine)
Mixed neuroendocrine non-neuroendocrine neoplasms (MiNENs) are rare tumors composed of two different histological components, one of which is of a neuroendocrine origin. Given its suggested underdiagnosis and consequent low prevalence, no clear diagnostic and treatment guidelines are available, and treatment usually follows regimens similar to that of the most aggressive component. On the other hand, multiple primary tumors (MPTs) are also rare neoplastic entities that usually confer a challenge regarding treatment options, for a regimen that comprises both the primary and the synchronous/metachronous malignancy should be used. Here, we discuss the challenging diagnostic and therapeutic management of a patient with an ileocecal MiNEN that presented along with a synchronous squamous non-small-cell lung cancer (SQ-NSCLC). The patient presented with intestinal obstruction symptoms for which he underwent an emergency resection of the ileocecal MiNEN. An initial CT scan showed an additional lung mass later identified as an SQ-NSCLC after bronchoscopy biopsy analysis. Given the rapid hepatic metastatic progression, palliative platinum-based chemotherapy was initiated, with an adequate response of the local and metastatic lesions of the MiNEN, but suggested platinum resistance and progression of the pulmonary neoplasm. Second-line treatment with pembrolizumab directed for the SQ-NSCLC was initiated; however, it was stopped after immune-mediated toxicities developed. A third-line chemotherapy scheme with carboplatin/gemcitabine was initiated, but central nervous system (CNS) progression developed, with the patient dying 11 months after initial diagnosis.